Call to Action: Librarians Promoting Health Literacy Assessments in Oral Communication. Issue 2 (3rd April 2019) - Tester, Emily; Grabeel, Kelsey Leonard; Oelschlegel, Sandy; Heidel, R. Eric; Russomanno, Jennifer
ABSTRACT: Effective oral communication is an integral part in the healthcare system. Conveying messages may prove to be a difficult task when health literacy barriers are present. At the University of Tennessee Medical Center (UTMC), a librarian-led task force was initiated to review health literacy related barriers. UTMC used The Health Literacy Environment of Hospitals and Health Centers tool, created by Rudd and Anderson in 2006 to evaluate oral communication. UTMC created a systematic plan for assessment including observation, interviews, and coding. Medical librarians serve a unique purpose in conducting research that can increase patient engagement and raise satisfaction.